(untitled) (Zaporizhzhia Historical Review, 2021)
The given article perfects on the history of the origin and development of the ìPure Baptistsî movement in Ukraine. Due to the archives the reasons of the origin and the cessation of the activity of ìPure Baptistsî have been revealed. The article also discusses the influence of ìPure Baptistsî on the creation of the ìInitiative groupî of Evangelical-Baptists and their oppositions to the official Church of Evangelical-Baptists in the USSR.